The Effect of a 10-MDP-Based Dentin Adhesive as Alternative for Bonding to Implant Abutment Materials - Carvalho, Paula C. K. [UNESP]; Almeida, Cláudia C M S; Souza, Rodrigo O. A.; Tango, Rubens Nisie [UNESP] (MDPI, 2022)
Bonding to different dental restorative materials is challenging. This study aimed to evaluate the effect of a 10-MDP-based dentin adhesive on the shear bond strength (SBS) of self-adhesive resin cement (RC) to implant abutment materials. One hundred and twenty specimens were obtained from zirconia (ZO), cobalt-chromium alloy (CoCr), and commercially pure titanium (Ti), which were treated as follows (n = 10): control group—non-treated (CG), 10-MDP-based dentin adhesive (SB), light-cured SB (SB-LC), and zirconia primer (ZP). Blocks of RC were buildup and, after 24 h, were tested for bond strength. Data of SBS (MPa) were submitted to two-way ANOVA and Tukey test (α = 0.05). There was no difference in SBS among materials for CG and ZP, higher SBS were recorded for Ti SB and Ti SB-LC compared to ZO upon the same surface treatments. For the comparisons among treatments, SB-LC showed the highest SBS for CoCr. For ZO and Ti, higher SBS were recorded with SB and SB-LC. No cohesive failures were observed. It was concluded that the surface treatment with 10-MDP-based materials increased the bond strength of the resin cement to abutment materials, which showed to be material dependent.
Keywords: 10-MDP; bond strength; dentistry; resin cement; titanium